Analysis of Corporate Frauds in the Indian Banking Sector - Tirumalaraju Naveen, G.V.Satya Sekhar (European Economic Letters (EEL), 2024)
The Banking Sector is the key sector for the country's overall development as it provides monetary resources for the needy, which includes retailers and corporates. The banking sector plays a vital role in improving our nation's GDP and we have witnessed the same since nationalization and liberalisation of our banking sector. At the same time, we have witnessed many fraud cases hit the news headlines and as per RBI reports, Indian banks have lost Rs. 5.74 lakh crores during the past decade and frauds by corporates contribute lion’s share in those figures. In this regard, our study analyzed the top fraud cases by corporates and suggested preventive measures for the same. We have reviewed fraud data taken a review period for the years 2013-2023 for our study and a sample from 146 bank employees from various banks. We have used content analysis to fulfill the objectives of this study. Our study found that political and bank top management pressures causes deviation in the bank's guidelines and also it was revealed that corrupt practices by bank staff are observed in some of the cases.